„Jan Mukařovský dla wszystkich”. O przekładach tekstów czeskiego teoretyka literatury i estetyki - Żygadło-Czopnik, Dorota (Przekłady Literatur Słowiańskich, 2020)
The subject of the analysis is the presence of Jan Mukarovsky’s texts in the field of Polish literary theory and aesthetics. The achievements of Czech structuralism, of which he was an outstanding representative, seem to be indisputable, since to this day they are a more or less conscious element of modern knowledge about literature. The Czech structuralism heritage still amazes and intrigues with its scale, and it undoubtedly continues to be a grateful object of research by Polish theoreticians and translators.